Diatom abundance from sediment cores (2008-2011) from six lakes of Sierra Nevada Mountains (Spain) - Carmen Pérez-Martínez; David Fernández-Moreno; Joana Llodrà-LLabrés; Laura Jiménez; Emilio Moreno; Eloísa Ramos-Rodríguez; José M Conde-Porcuna (PANGAEA, 2023)
This dataset presents relative abundance data of subfossil diatoms obtained from sediment cores retrieved from six lakes at Sierra Nevada Mountains (Granada, Spain) during 2008 and 2011. The files show data over the past 180 years approximately. Sediment cores were taken from the deepest part of the lake by a slide-hammer gravity corer (Aquatic Research Instruments, USA), with a 6.9 cm inner diameter during the summer of 2011, except for Río Seco Lake core which was sampled in 2008. The cores were sectioned on-site into 0.25 cm thick layers for the upper sections of the cores and into 0.5 cm intervals for the remainder of the cores, except for Río Seco Lake core which was sectioned at 0.5 cm contiguous intervals for the entire core length. Sediment cores were dated using gamma spectrometry (DSPec, Ortec®) techniques by measuring activities of radioisotopes (210Pb, 214Bi and 137Cs) and sediment ages were estimated from unsupported 210Pb activities using the constant rate of supply (CRS) model. Diatom samples were processed by digesting sediment samples with a 50:50 mixture solution of H2SO4 and HNO3 and mounted onto slides with Naphrax®. For each sample, a minimum of 300 diatom valves were counted using a Leica microscope fitted with a 100 exttimes fluotar objective (N.A. = 1.4) and using differential interference contrast optics under oil-immersion at 1000 exttimes magnification. Diatoms were identified to the species level or lower using a selection of taxonomic sources and diatom counts were expressed as a percent abundance relative to the total number of diatom valves counted in each sedimentary interval.